Variation of plant CSR strategies across a precipitation gradient in the alpine grasslands on the northern Tibet Plateau - Yu, Jialuo; Hou, Ge; Zhou, Tiancai; Shi, Peili; Zong, Ning; Sun, Jian (The Science of the total environment, 2022)
Identifying ecological strategies based on functional traits can help us better understand plants' adaptations and changes in ecological processes, and thus predict the impact of climate change on ecosystems, especially in the vulnerable alpine grasslands. Herein, we investigated the plant CSR strategies of four grassland types (alpine meadows, AM; alpine meadow steppes, AMS; alpine steppes, AS; and alpine desert steppes, ADS) and its functional groups (grasses, sedges, legumes, and forbs) along the east-to-west gradient of decreasing precipitation on the northern Tibetan grasslands by using Grime's CSR (C: competitor, S: stress tolerator, and R: ruderal) analysis. Although alpine grasslands were dominated by S-strategy, our results also indicated that AM with higher water, nitrogen (N) and phosphorus (P) availability had significantly lower S-strategy values and relatively higher C- and R-strategy values (C: S: R = 6: 63: 31 %) than those in AMS (C: S: R = 3: 94: 3 %,), AS (C: S: R = 3: 87: 10 %), and ADS (C: S: R = 1: 94: 5 %). The CSR strategy values of forbs and legumes showed greater variability compared with grasses and sedges in the environmental gradient. Furthermore, water variability on the precipitation gradient eventually affected plant traits and CSR strategies through soil N and P availability and pH. Our findings highlighted that plant CSR strategies were regulated by the availability of soil resources, and plants adopted more flexible adaptation strategies in relatively resource-rich environments. This study sheds light on the mechanisms of plant adaptation to the changing environment in the alpine grasslands. [Display omitted] •S-strategy species dominate in the alpine grasslands.•Higher water, nitrogen (N) and phosphorus (P) availability had significantly lower S-strategy values.•Forbs and legumes adopted more flexible strategies compared with grasses and sedges.•Water variability affected plant traits and CSR strategies through soil N and P availability and pH.